Fates of the Old Czech Annals [Text F] - Černá, Alena M. (Poznańskie Studia Slawistyczne, 2018)
The collection of Hussite chronicles called Old Czech Annals contains more than thirty manuscripts some of which have been left out of the research spotlight. One of them is the Czech written text F (called “of Stockholm”) from the second half of the 15th century, currently stored under the signature G 10, no. 432 in the Moravian Municipal Archive in Brno, nevertheless, until 1878, it had been held in Stockholm as a spoil. The text F describes the course of events on the Czech territory from the years 1393 to 1453. Particular emphasis is laid on the events taking place during the Hussite revolution (after 1419) narrated, from the perspective of moderate Utraquism, by an anonymous Prague chronicler. Even though he, in his descriptions, consciously evades to include his evaluation of the events, striving for being an objective and impartial, unbiased observer, it is possible, at times, to read his attitude and opinion from his language rendering, which we instantiate with citations from the manuscript. A copy of the manuscript was acquired during its brief borrowing from Sweden to Prague in 1819 by Václav Hanka (1791–1861), a prominent representative of the Czech National Revival. The copy is stored in the National Museum Library, signature III F 9.